Year-Round Aggregation of Sandbar Shark, Carcharhinus plumbeus (Nardo, 1827), in Boncuk Cove in the southern Aegean Sea, Turkey (Carcharhiniformes: Carcharhinidae). Issue 1 (2nd January 2019) - Filiz, Halit
Abstract : The present study provided a two-years assessment to understand the seasonal fluctuations of aggregation of the Sandbar Shark, Carcharhinus plumbeus, in Boncuk Cove in the southern Aegean Sea. Underwater Visual Censuses (UVC) revealed that the species is present in the cove throughout the year but form aggregations only between March and November. Aggregation in groups was observed at a daily sea temperature above 18.1°C and this indicated a possible lower threshold for aggregations for Boncuk Cove population.